Peningkatan Kemampuan Mengecap dengan Media Jari pada Anak Kelompok B TK Pertiwi Gading Kecamatan Tanon Kabupaten Sragen - Ngadiyem, Ngadiyem (Didaktika, 2022)
Fingerprint creation is a drawing technique using fingerprints, this activity is very popular for young children, because this activity is like playing activities, but has meaning for children. The formulation of the problem in this research is "How to Increase the Ability to Taste with Finger Media in Group B Children of Pertiwi Gading Kindergarten, Tanon District, Sragen Regency? This study aims to determine the Improved Tasting Ability with Finger Media in Group B Children of Pertiwi Gading Kindergarten, Tanon District, Sragen Regency. The research subjects were taken from group B students of TK Pertiwi Gading, Tanon District, Sragen Regency, with a total of 31 children consisting of 15 boys and 16 girls.Datacollection methods used observation and documentation methods. Based on statistical calculations, it was obtained that pre-action in 1 class the average percentage of children was 41.29% with the Starting Development (MB) assessment criteria, and the first cycle increased by 67.31% with the Development According toExpectations (BSH) criteria. Tasting activities increased but the results obtained were not optimal because they had not reached the mutually agreed success indicator of 80%. For this reason, researchers and collaborating partners held a follow-up cycle, namely cycle II, the results achieved in research in cycle II, the average percentage of children in 1 class was 84.52%. With the Very Well Developed (BSB) assessment criteria. the average percentage obtained by children in 1 class has increased, for this reason, researchers have succeeded and achieved mutually agreed indicators and it is proven that finger media can increase the ability to taste with group B children TK Pertiwi Gading Tanon District Sragen Regency